Predictive effect of social apperance anxiety on compulsive online buying in young adults - Tabak, Melisa Yudum; Kahraman, Süleyman (Journal of Dependence, 2022)
Objective: The aim of this study, is to determine the predictive effect of social appearance anxiety on compulsive online buying in young adults. Method: 421 young adults voluntarily participated in the study. In this study, which eas based on the relational screening model, the Social Appearance Anxiety Scale and the Compulsive Online Buying Scale were used. Results: Social appearance anxiety and gender was found to predict compulsive online buying by %13,2 in young adults. In terms of demographic variables social appearance anxiety and compulsive online buying were found to be significantly higher in male, self-assessed weight, any physical ailment affecting their appearance, psychological disorders and online shopping because they did not want to go to the store. Conclusion: This may indicate that individuals with social appearance anxiety may tend to compulsive online buying.